Pengaruh Struktur Kepemilikan, Kebijakan Dividen, Dan Sales Growth Terhadap Kinerja Keuangan Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2021 - Amelia Indriani Puspitasari; Sri Rahayuningsih (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to determine the impact of ownership structure, dividend policy, and sales growth on financial performance, as well as the simultaneous effect of ownership structure, dividend policy, and sales growth on financial performance. The data used in this study consists of secondary data derived from annual financial reports which can be accessed via the official website www.idx.co.id. The population used in this study are pharmaceutical companies listed on the Indonesia Stock Exchange in the 2018-2021 period. The sample used in this study uses a saturated sampling method. The analysis used in this study is multiple linear regression, using SPSS 22 software. The results of this study indicate that dividend policy has an effect on financial performance while ownership structure and sales growth have no effect on financial performance